If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 = n + -11 Reorder the terms: 14 = -11 + n Solving 14 = -11 + n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. 14 + -1n = -11 + n + -1n Combine like terms: n + -1n = 0 14 + -1n = -11 + 0 14 + -1n = -11 Add '-14' to each side of the equation. 14 + -14 + -1n = -11 + -14 Combine like terms: 14 + -14 = 0 0 + -1n = -11 + -14 -1n = -11 + -14 Combine like terms: -11 + -14 = -25 -1n = -25 Divide each side by '-1'. n = 25 Simplifying n = 25
| X^2+2x-195= | | d-8=20 | | 2x=-3y+4 | | x/5=7/15 | | 5-y=3-x | | 5(3m+8)=175 | | 3(8+4x)=30-10x | | 4m-4=4m+2 | | 217=16t^2+32t | | 7+c/3=13 | | h=-16t^2+80t+4.5 | | 3u^2+8u=-5 | | -(-8x-6)=6x-22 | | 3x-3/6 | | 2-y=12-2x | | (4x)^2*2x^3/x | | 12-3(x+2)=x-2 | | 3x-3=x-5 | | -1x+12=-12 | | 12g^2+6g-6=0 | | -2x-4y=-8 | | -12x+6=-2(5x-4) | | 12g-8g+6g-6=0 | | a^2=2x-4 | | x*ln(x)-24+6*ln(x)-4*x=0 | | 4(x+3)=-5(x+4)+8 | | 5t^2+10t=40 | | x*ln(x)-24+6ln(x)-4x=0 | | 3x+4x+50=101 | | 2x+3=x+x-4 | | 1/4=2x-4 | | 8y+y^2=48 |